The Marharoan Bolon Tradition as a Socio-Ecological Practice in the Sustainable Development of the Simalungun Community - Nahwa Zainab Marpaung (Journal of Sumatera Sociological Indicators, 2026)
Local wisdom plays an important role in building harmonious relationshipsbetween communities and the environment. Marharoan Bolon, a tradition ofmutual cooperation unique to the Simalungun community, reflects socioecological practices that embody the values of togetherness, solidarity, and carefor the environment. This study aims to analyze the role of this tradition insupporting sustainable development, particularly through communityparticipation in environmental management. The method used is a descriptivequalitative approach through literature study and conceptual analysis from anecological sociology perspective. The results show that Marharoan Bolonfunctions as a social mechanism that strengthens community cohesion while alsoserving as an adaptive strategy in maintaining the sustainability of naturalresources. This tradition encourages active community involvement in villageinfrastructure development, land maintenance, and collective environmentalpreservation. However, the dynamics of modernization and changes in socialstructure pose significant challenges to the sustainability of these traditionalvalues. Therefore, the preservation of Marharoan Bolon needs to be integratedwith community-based development policies so that it can adapt to thecontemporary socio-ecological context without losing its local cultural meaning.Keyword: Marharoan Bolon, Simalungun community, local wisdom, sustainabledevelopment